Fastest non-ionic azo dyes and transfer of their thermal isomerisation kinetics into liquid-crystalline materials - Garcia-Amorós, J. (2016)
Push-pull bithienylpyrrole-based azo dyes exhibit thermal isomerisation rates as fast as 1.4 μs in acetonitrile at 298 K becoming, thus, the fastest neutral azo dyes reported so far. These remarkably low relaxation times can be transferred into liquid-crystalline matrixes enabling light-triggered oscillations in the optical density of the final material up to 11 kHz under ambient conditions.